THE MORE FAVORABLE CONTRAVENTION LAW IN THE CONTEXT OF RO-E-TRANSPORT: CHALLENGES AND CRITICAL CONSIDERATIONS - Narcisa-Victoria DĂRĂBAN (Challenges of the Knowledge Society, 2025)
The year 2024 was an extremely dynamic one regarding the changes made to the GEO no. 41/2022, which establishes the national system for monitoring road freight transport, RO-e-transport, particularly concerning the sanctioning regime. The achievement of the system's goal to monitor the transport of goods, prevent tax evasion, increase tax and fee collection, and combat illicit trade, led tax control authorities, encouraged by the regulatory framework, to adopt an abusive approach in terms of the contravention sanctions imposed. Courts across the country have been dealing with complaints based on GEO no. 41/2022, with petitioners criticizing the sanctions applied in terms of their proportionality. From the concept of the more favorable contravening law to decontraventionalisation and constitutional exceptions, judicial discussions have been, and continue to be, extensive, sparked by the application and adherence to the rules imposed by the RO-e-transport system. This article aims to review the main modifications to art. 13 of GEO no. 41/2022, which regulates contraventions related to the monitoring of road freight transport under RO-e-Transport, provide an analysis of the current judicial practice, and offer critical considerations regarding the applicable regulatory framework.